A positive electrode material, a preparation method and application thereof

CN122224821BActive Publication Date: 2026-10-16REPT BATTERO ENERGY CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610702541.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-21
Publication Date
2026-10-16
Estimated Expiration
2046-05-21

AI Technical Summary

Technical Problem

然而,该体系在实际应用中面临双重挑战:(1)普遍存在电子电导率低(通常低于 10-6S/cm)、钠离子扩散速率慢的问题,直接导致电池倍率性能不足 —— 高倍率充放电时容量急剧衰减,无法满足动力或储能场景的快速充放电需求

Benefits of technology

本发明采用 “多孔内核-导电外层-弹性缓冲层” 三级结构,区别于现有专利单一核壳/多孔结构,每一层结构对应明确作用:①多孔内核(多元金属元素掺杂NASICON多孔材料),多元金属高熵掺杂优化了材料电子结构,提升了氧化还原电位的稳定性,进一步减少高电压下的界面退化,其多孔结构有利于构建离子传输通道,提高离子迁移动力学;②导电外层可以提高材料的电子电导率,具体的,导电外层为NaaTibOc时,利用 Ti-O-Fe/Mn 界面化学键提升结合力,提高导电性;导电外层为Na3V2(PO4)3时,其钒(V)元素通常以+3价和+4价的混合价态存在,利用 V3+/V4+混合价态的电子跳跃机制,使得该材料具有较高的电子电导率;且本身也属于 NASICON 结构,拥有由八面体和四面体共顶点连接形成的坚固三维骨架,这种结构提供了宽阔的钠离子迁移通道;③弹性缓冲层通过 “PI、PVDF或PAA形变缓冲+ Al2O3、HfO2或TiO2刚性支撑”,抑制循环微裂纹,解决体积膨胀问题。导电外层与弹性缓冲层形成致密包覆,减少内部NASICON多孔材料与电解液的直接接触,抑制副反应发生,进而提高容量以及循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122224821B_ABST
    Figure CN122224821B_ABST
Patent Text Reader

Abstract

The application discloses a positive electrode material and a preparation method and application thereof; a multi-element doped NASICON system with a three-level coordinated structure of a porous inner core, a conductive outer layer and an elastic buffer layer is constructed, the multi-element doped NASICON is taken as a material core, the conductive outer layer is coated to improve the conductivity, the elastic buffer layer of the outer layer has excellent deformation self-adapting capacity, can absorb expansion stress and prevent the electrode structure from cracking, and the conductive outer layer and the elastic buffer layer form dense coating to isolate the direct contact between the internal NASICON porous material and electrolyte and inhibit the occurrence of a side reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cathode materials and preparation technology for new energy batteries, specifically to a cathode material, its preparation method, and its application. Background Technology

[0002] Sodium-ion batteries (SIBs) have shown broad application prospects in energy storage, power supply and other fields due to the advantages of abundant sodium resources and low cost. Sodium superionic conductor (NASICON) type phosphate cathode materials have attracted much attention due to their unique three-dimensional open framework structure, excellent thermal stability and flexible composition adjustability. However, this system faces two challenges in practical applications: (1) the electronic conductivity is generally low (usually below 10). -6 The slow diffusion rate of sodium ions (S / cm) directly leads to insufficient battery rate performance—the capacity decays sharply during high-rate charging and discharging, failing to meet the rapid charging and discharging requirements of power or energy storage scenarios. (2) The radius of sodium ions (1.02 Å) is much larger than that of lithium ions (0.76 Å), which easily causes lattice distortion and volume expansion when inserted into / extracted from the cathode material. The volume expansion rate of traditional NASICON materials often exceeds 8%, which can lead to electrode cracking and active material shedding after repeated cycles, ultimately resulting in rapid capacity decay and shortened cycle life. Recently, the concept of high-entropy (HE) has been extended to the design of sodium-ion battery cathodes to improve electrochemical performance, but research on HE strategies for NASICON phosphate cathode systems is still insufficient. Therefore, developing high-energy-density, long-life NASICON-type cathode materials has become a key task. Summary of the Invention

[0003] To address the shortcomings of existing technologies, the present invention aims to provide a cathode material, its preparation method, and its applications. The present invention constructs a three-tiered synergistic structure of a multi-element NASICON system consisting of a porous core, a conductive outer layer, and an elastic buffer layer. This multi-element NASICON-doped material (such as Fe-Mn-Cr, Fe-Mn-V, or Mn-Ni-Co ternary doped NASICON) serves as the core, with a conductive outer layer (such as Na2Ti3O7 or Na2Ti6O7) as the core. 13 Na4Ti5O 12 Alternatively, it can be coated with Na3V2(PO4)3 to improve conductivity; the outermost elastic buffer layer (such as PI-Al2O3, PVDF-HfO2, PAA-TiO2) has excellent deformation self-adaptation ability, which can absorb expansion stress and prevent the electrode structure from cracking; at the same time, the conductive outer layer and the elastic buffer layer form a dense coating, reducing the direct contact between the internal NASICON porous material and the electrolyte and suppressing the occurrence of side reactions.

[0004] Specifically, the object of the present invention is achieved by the following solutions: The present invention provides a positive electrode material, and the positive electrode material has a three-level structure of a porous inner core - a conductive outer layer - an elastic buffer layer from inside to outside; wherein the porous inner core is a NASICON porous material doped with multiple metal elements; the conductive outer layer coats the porous inner core, and the chemical general formula of the conductive outer layer is Na a Ti b O c or Na a V d (PO4)3, 2≤a≤4, 3≤b≤6, 7≤c≤13, 0<d≤2; the outermost elastic buffer layer is A-M m O n , A is PI, PVDF or PAA, M is any one selected from Al, Hf or Ti, and 1≤m≤2, 2≤n≤3.

[0005] As one embodiment, the metal doping elements of the NASICON porous material are selected from three or more of Fe, Mn, Cr, V, Ni and Co. Ternary doping of Fe-Mn-Cr, Fe-Mn-V or Mn-Ni-Co is preferred.

[0006] As one embodiment, the metal doping elements are Fe, Mn and Cr, and the molar ratio among Fe, Mn and Cr is 5:2-3:2-3.

[0007] As one embodiment, the chemical formula of the NASICON porous material is Na (3+y) Fe x Mn y Cr z (PO4)3, wherein x+y+z=2.

[0008] As one embodiment, the metal doping elements are Fe, Mn and V, and the molar ratio among Fe, Mn and V is 5:2-3:2-3.

[0009] As one embodiment, the conductive outer layer is Na2Ti3O7, Na2Ti6O 13 , Na4Ti5O 12 or Na3V2(PO4)3.

[0010] As one embodiment, M in the elastic buffer layer m O n is Al2O3, HfO2 or TiO2. As a specific embodiment, the elastic buffer layer is PI-Al2O3, PVDF-HfO2 or PAA-TiO2.

[0011] The present invention also provides a method for preparing a cathode material, the method comprising the following steps: S1. Preparation of porous cores: S1-1. Add sodium dihydrogen phosphate to a mixed metal salt solution containing multiple metal ions, stir, and adjust the pH to 2-3; add a pore-forming agent, heat and stir until a precursor solution is formed, and filter for later use; S1-2: After the filtered precursor solution is ultrasonically atomized, the droplets are dried and then calcined to obtain multi-metal element doped NASICON porous material. S2, Conductive outer coating: Sodium hydroxide was added to the titanium source solution and stirred to form a stable coating solution. The coating solution was then ultrasonically atomized and sprayed onto the surface of the porous core prepared by S1. The reaction was carried out at 700-800℃ to form a conductive coating layer, thus obtaining the coating product. The specific reaction time could be 2-3 hours. Alternatively, sodium acetate can be added to the vanadium source solution and stirred to form a stable coating solution; the coating solution is then ultrasonically atomized and sprayed onto the surface of the porous core prepared by S1, and reacted at 700-800℃ to form a conductive coating layer to obtain the coating product; the specific reaction time can be 2-3 hours. S3. Preparation of the elastic buffer layer: Add M to a solution containing PI, PVDF, or PAA m O n The powder is dispersed to form a buffer layer slurry; the buffer layer slurry is ultrasonically atomized and sprayed onto the surface of the coating product obtained in step S2, and then cured to obtain the positive electrode material.

[0012] In some implementation examples, step S1-1, in the presence of Fe³ + Mn² + Cr³ + Mixed metal salt solutions, containing Fe³ + Mn² + V 5+ Mixed metal salt solutions or solutions containing Mn² + Ni² + Co 2+ Sodium dihydrogen phosphate was added to a mixed metal salt solution and stirred. The pH was adjusted to 2-3 with dilute acid. A pore-forming agent was added, and the mixture was heated and stirred until a transparent precursor solution was formed. The solution was then filtered and set aside. Step S1-2: The filtered precursor solution was ultrasonically atomized, and the droplets were dried and then calcined to obtain Fe-Mn-Cr, Fe-Mn-V, or Mn-Ni-Co ternary doped NASICON porous materials.

[0013] In one implementation scheme, in step S1-1, the mixed metal salt solution is a mixed aqueous solution of nitrates doped with metal elements. The manganese content in the mixed metal salt solution is 0.1-0.2 mol / L.

[0014] As one implementation scheme, in step S1-1, sodium dihydrogen phosphate is added and stirred at a speed of 800-1200 rpm for 30-40 min at room temperature; the mass ratio of sodium dihydrogen phosphate to manganese nitrate is 10:1.5-4.

[0015] As one implementation scheme, in step S1-1, the pore-forming agent is polyethylene glycol, and the mass ratio of polyethylene glycol to sodium dihydrogen phosphate is 1:5-8. The heating and stirring is carried out by heating to 50-70℃ and stirring at a constant temperature for 30-40 minutes.

[0016] As one implementation scheme, in step S1-1, the filtration uses a 0.20-0.22μm filter membrane.

[0017] As one implementation scheme, in steps S1-2, the ultrasonic atomization frequency is 12-18 MHz and the peristaltic flow rate is 1-3 mL / min.

[0018] As one implementation scheme, in steps S1-2, the drying temperature is 180-220 ℃, and the drying time is 4-6 h.

[0019] As one implementation scheme, in steps S1-2, the calcination temperature is 720-780 ℃, and the calcination time is 8-10 h.

[0020] As one implementation, in steps S1-2, the calcination is carried out in an inert atmosphere with a gas flow rate of 45-55 mL / min.

[0021] As one implementation scheme, in steps S1-2, the atomized droplets enter a tubular furnace for drying and calcination; the tubular furnace is heated to 180-220℃ for 4-6 hours in the drying section and to 720-780℃ for 8-10 hours in the calcination section, during which an inert atmosphere is introduced and the gas flow rate is 45-55 mL / min.

[0022] As one implementation scheme, in step S2, the titanium source solution is prepared by adding tetrabutyl titanate to a solvent to dissolve it, and then adjusting the pH of the solution to 1-2. In some implementation examples, the titanium source solution is formed by adding 7-8g of tetrabutyl titanate to 100mL of ethanol, stirring at room temperature for 30-40min, adding dilute hydrochloric acid dropwise to adjust the pH to 1-2, and continuing to stir for 30-40min.

[0023] As one implementation scheme, in step S2, the vanadium source solution is prepared by adding ammonium metavanadate and ammonium dihydrogen phosphate to a solvent, stirring, and then adding citric acid, stirring until a clear solution is formed. In some implementation examples, the vanadium source solution is prepared by adding 4.0-4.5 g of ammonium metavanadate and 6.0-6.5 g of ammonium dihydrogen phosphate to 100 mL of deionized water, stirring at room temperature for at least 25 min, adding 5-8 g of citric acid, and stirring until the solution is clear. Then, 4-6 g of sodium acetate is added, and stirring is performed until a stable coating solution is formed.

[0024] As one implementation scheme, in step S2, before spraying the coating liquid onto the surface of the porous core prepared in S1 after ultrasonic atomization, the porous core prepared in S1 is kept at 250-350℃ for 30-40 minutes to remove surface adsorbed water.

[0025] As one implementation scheme, in step S2, the ultrasonic atomization frequency is 10-12MHz and the peristaltic flow rate is 0.7-1mL / min.

[0026] In some implementation examples, the coating is carried out in a tube furnace. The porous core prepared by S1 is placed in the preheating section of the tube furnace and kept at 250-350℃ for 30-40 min to remove surface adsorbed water. The ultrasonic atomization frequency is 10-12MHz and the peristaltic flow rate is 0.7-1mL / min.

[0027] In some implementation examples, in step S2, when the conductive outer layer is Na2Ti3O7, the corresponding reaction temperature is 700-800℃; when the conductive outer layer is Na2Ti6O7... 13 The corresponding reaction temperature is 750-800℃; the conductive outer layer is Na4Ti5O. 12 When the outer conductive layer is Na3V2(PO4)3, the corresponding reaction temperature is 700-750℃; when the outer conductive layer is Na3V2(PO4)3, the corresponding reaction temperature is 750-800℃.

[0028] In one implementation, in step S3, the solution comprising PI, PVDF, or PAA is formed by adding PI, PVDF, or PAA powder to a solvent, heating to 70-90°C, and stirring until the PI, PVDF, or PAA is at least partially dissolved. In some implementation examples, the aqueous solution comprising PI is formed by adding 2-4 g of polyimide powder to 100 mL of deionized water, heating to 70-90°C, and stirring for 40-60 min until the PI is partially dissolved. The aqueous solution comprising PAA is formed by adding 2-4 g of PAA powder to 100 mL of deionized water, heating to 50-70°C, and stirring for 40-60 min until the PAA is dissolved. The solution comprising PVDF is formed by adding 2-4 g of PVDF powder to 100 mL of NMP, heating to 50-70°C, and stirring for 4-6 h until the PVDF is dissolved.

[0029] As an implementation scheme, in step S3, M m O n The mass ratio of PI, PVDF, or PAA is 1:2-4.

[0030] As one implementation, in step S3, the dispersion speed is 5000-7000 rpm and the dispersion time is 30-40 min.

[0031] As one implementation scheme, in step S3, the viscosity of the buffer layer slurry is controlled at 500~800 mPa. s.

[0032] In one implementation, step S3 involves curing in a tube furnace. The coated product obtained in step S2 is placed in the tube furnace, and the furnace temperature is lowered to the temperature required for complete curing of PI, PVDF, or PAA. Specifically, the curing temperature for PI is 150-180℃; and the curing temperatures for PVDF and PAA are 100-140℃.

[0033] In some implementation examples, when the elastic buffer layer is PI (polyimide)-Al2O3, it is kept at 150-180℃ until the PI is completely cured. When the elastic buffer layer is PVDF (polyvinylidene fluoride)-HfO2 (hafnium dioxide), it is kept at 100-140℃ until the PVDF is completely cured. When the elastic buffer layer is PAA (polyacrylic acid)-TiO2, it is kept at 100-140℃ until the PAA is completely cured.

[0034] As one implementation scheme, in step S3, the atomization frequency of ultrasonic atomization is 8-10MHz, and the peristaltic flow rate is 0.6-0.8mL / min.

[0035] In one implementation, in step S3, the cured product is cooled to room temperature, ground, and sieved to obtain the cathode material. In some implementation examples, the cured product is cooled to room temperature, gently ground with an agate mortar to avoid damaging the buffer layer, and then sieved through a 180-200 mesh sieve to obtain the cathode material.

[0036] The present invention also provides a positive electrode sheet, wherein the active material of the positive electrode sheet is the aforementioned positive electrode material, or a positive electrode material prepared by the aforementioned method.

[0037] As one implementation, in the electrode slurry of the positive electrode sheet, the mass ratio of the aforementioned positive electrode material, conductive material, and binder is 7-8:1-2:1-2.

[0038] Furthermore, batteries using the aforementioned positive electrode as the positive electrode are also within the scope of protection of this invention.

[0039] The present invention also provides a battery comprising the aforementioned positive electrode material, or comprising a positive electrode material prepared by the aforementioned method.

[0040] Compared with the prior art, the present invention has the following beneficial effects: This invention employs a three-tiered structure of "porous core - conductive outer layer - elastic buffer layer," which differs from existing patents' single core-shell / porous structures. Each layer has a specific function: ① The porous core (a multi-metal doped NASICON porous material) optimizes the material's electronic structure through high-entropy doping of multi-metals, improving the stability of the redox potential and further reducing interface degradation under high voltage. Its porous structure facilitates the construction of ion transport channels and enhances ion migration kinetics; ② The conductive outer layer improves the material's electronic conductivity. Specifically, the conductive outer layer is Na... a Ti b O c When the Ti-O-Fe / Mn interface chemical bonds are utilized to enhance the bonding force and improve conductivity; when the conductive outer layer is Na3V2(PO4)3, its vanadium (V) element usually exists in a mixed oxidation state of +3 and +4, utilizing V 3+ / V 4+ The mixed-valence electron hopping mechanism gives this material high electronic conductivity; it also belongs to the NASICON structure, possessing a robust three-dimensional framework formed by octahedrons and tetrahedrons sharing common vertices, providing ample channels for sodium ion migration; ③ The elastic buffer layer, through "PI, PVDF or PAA deformation buffer + Al2O3, HfO2 or TiO2 rigid support," suppresses cyclic microcracks and solves the volume expansion problem. The conductive outer layer and the elastic buffer layer form a dense coating, reducing direct contact between the internal NASICON porous material and the electrolyte, suppressing side reactions, and thus improving capacity and cycle life. Attached Figure Description

[0041] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 SEM images of the cathode materials prepared in Examples 1-3 and Comparative Example 1; wherein, a, Example 1 (Fe 3+ :Mn 2 + :Cr 3+ =5:3:2); b. Example 3 (Fe 3+ :Mn 2+ :Cr 3+ =5:2.5:2.5); c. Example 2 (Fe 3+ :Mn 2+ :Cr 3+ =5:2:3); d. Comparative Example 1 (uncoated -Fe 3+ :Mn 2+ :Cr 3+ =5:3:2); Figure 2 The EIS test results are for the batteries corresponding to the positive electrode materials prepared in Examples 1-3 and Comparative Example 1. The measurement frequency range is 106~10-3Hz, and the state of charge of the battery is 100%SOC. Figure 3 SEM images of the positive electrode sheets of the batteries corresponding to the positive electrode materials prepared in Example 1 and Comparative Example 1 after 200 cycles. Figure 4 This is a TEM image of the composite material obtained from the high-conductivity outer layer (Na2Ti3O7) coating process in Example 1. Figure 5 The image shows the XRD pattern of the composite material obtained by the high conductivity outer layer (Na2Ti3O7) coating process in Examples 1-3. Detailed Implementation

[0042] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several changes and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0043] Example 1 This embodiment provides a novel sodium-ion composite electrode preparation method; the method for preparing the cathode material includes the following steps: I. Preparation of porous cores (Fe-Mn-Cr ternary doped NASICON) Take 24.4g of ferric nitrate (Fe(NO3)3·9H2O), 9.1g of manganese nitrate (Mn(NO3)2·4H2O), and 9.7g of chromium nitrate (Cr(NO3)3·9H2O) and place them in 300 mL of deionized water (molar ratio Fe:Mn:Cr=5:3:2). Place the solution on a magnetic stirrer (1000 rpm) and stir at room temperature for 40 min until completely dissolved to form a mixed metal salt solution. Then add 35.5g of sodium dihydrogen phosphate to the mixed metal salt solution and continue stirring for 80 min. During this period, adjust the pH to 2-3 with dilute nitric acid (to prevent hydrolysis and precipitation of metal ions). Add 5g of pore-forming agent polyethylene glycol (PEG-2000), heat to 60℃, and stir at a constant temperature for 40 min to form a transparent and homogeneous precursor solution. Finally, filter the solution through a 0.20μm filter membrane to remove undissolved impurities and avoid clogging of the atomizing nozzle.

[0044] The tubular furnace was heated to 200℃ in the drying section (5h) and to 750℃ in the calcination section (9h), with an argon atmosphere introduced (flow rate 50mL / min). The ultrasonic nebulizer frequency was adjusted to 15MHz, and the peristaltic pump flow rate was set to 2mL / min to ensure uniform droplet entry into the tubular furnace after atomization. Spraying process: The filtered precursor solution was poured into the peristaltic pump storage tank, the equipment was started, and the droplets entered the drying section of the tubular furnace after ultrasonic atomization, where the moisture evaporated rapidly and the PEG was initially softened. Subsequently, it entered the calcination section, where the PEG was completely decomposed (generating CO2 and H2O, forming pores), and the metal salt reacted with the sodium source to generate the NASICON structure. Product collection: A cyclone separator was connected to the outlet end of the tubular furnace to collect the black powdery core product Na. 3.6 Fe 1.0 Mn 0.6 Cr 0.4 (PO4)3.

[0045] Second, a highly conductive outer layer (Na2Ti3O7) is applied: Take 100 mL of ethanol, add 7.4 g of tetrabutyl titanate, stir at room temperature for 40 min, add 5 mL of dilute hydrochloric acid (to adjust the pH to 1-2), and continue stirring for 40 min to form a titanium source solution; add 4 g of sodium hydroxide (to provide Na). +Stir for 30 minutes to form a stable coating solution. Core pretreatment: The porous core powder prepared in the first step is evenly spread in a quartz boat (thickness ≤ 5 mm), placed in the preheating section of a tube furnace (300℃), and kept at this temperature for 40 minutes to remove surface adsorbed water; start the peristaltic pump and atomizer, adjust the atomizer frequency to 12 MHz, reduce the peristaltic pump flow rate to 0.7 mL / min, and evenly spray the coating solution onto the core surface after atomization (22 g core, approximately 120 mL coating solution). React at 800℃ for 2 hours, and tetrabutyl titanate hydrolyzes to generate Na2Ti3O7, forming a Na2Ti3O7 coating layer; TEM observation results of the sample ( Figure 4 The surface has a continuous and clear Na2Ti3O7 coating layer.

[0046] III. Preparation of the elastic buffer layer (PI-Al2O3): 1. Take 100 mL of deionized water, add 3 g of polyimide (PI) powder, heat to 80 °C, and stir for 60 min until the PI is partially dissolved, forming a viscous solution; add 1 g of Al2O3 powder, and disperse using a high-speed disperser (6000 rpm) for 40 min to form a uniform buffer slurry; the viscosity of the buffer slurry is measured to be 700 mPa using a viscometer. s.

[0047] 2. Buffer layer coating operation: The product coated in the second step is placed in a tube furnace, the temperature of the tube furnace is set to 180℃, the equipment is started, the atomizer frequency is adjusted to 9MHz, the peristaltic pump flow rate is set to 0.7mL / min, the buffer layer slurry (19.0mL) is atomized and sprayed on its surface, and kept at 180℃ for 1h to completely solidify PI and form a dense buffer layer with Al2O3; the product is taken out from the tube furnace, cooled naturally to room temperature, and gently ground with an agate mortar (to avoid damaging the buffer layer), and passed through a 200-mesh sieve to obtain the final positive electrode material with a porous core, conductive outer layer and elastic buffer layer.

[0048] Example 2 The difference between this embodiment and Example 1 is that in step one, 24.4g of ferric nitrate, 6.1g of manganese nitrate, and 14.5g of chromium nitrate were placed in 300 mL of deionized water (molar ratio Fe:Mn:Cr = 5:2:3); the mass of sodium dihydrogen phosphate added was 33.5g, and the product obtained was Na. 3.4 Fe 1.0 Mn 0.4 Cr 0.6 (PO4)3.

[0049] Example 3 The difference between this embodiment and Embodiment 1 is that in step one, 24.4g of ferric nitrate, 7.6g of manganese nitrate, and 12.1g of chromium nitrate are placed in 300°C deionized water (molar ratio Fe:Mn:Cr = 5:2.5:2.5), and the mass of sodium dihydrogen phosphate added is 34.5g. The product obtained is Na. 3.5 Fe 1.0 Mn 0.5 Cr 0.5 (PO4)3.

[0050] Example 4 The difference between this embodiment and Example 1 is that in step one, 24.4g of ferric nitrate, 9.1g of manganese nitrate, and 2.8g of ammonium metavanadate are dissolved in 300 mL of deionized water by heating (molar ratio Fe:Mn:V = 5:3:2); the mass of sodium dihydrogen phosphate added is 31.5g, and the product obtained is Na. 3.2 Fe 1.0 Mn 0.6 V 0.4 (PO4)3.

[0051] Example 5 The difference between this embodiment and Embodiment 1 lies in step two, where a highly conductive outer layer (Na3V2(PO4)3) is applied: Take 100 mL of deionized water, add 4.2 g of ammonium metavanadate and 6.2 g of ammonium dihydrogen phosphate, and stir at room temperature for 30 min; add 6 g of citric acid (complexing agent and carbon source), and continue stirring for 1 h until the solution is clear; add 4.5 g of sodium acetate (to provide Na). + Stir for 30 minutes to form a stable coating solution.

[0052] Core pretreatment: The porous core powder prepared in the first step is evenly spread in a quartz boat (thickness ≤ 5 mm), placed in the preheating section of a tube furnace (300 °C), and kept at this temperature for 40 min to remove surface adsorbed water; the peristaltic pump and atomizer are started, the atomizer frequency is adjusted to 12 MHz, the peristaltic pump flow rate is reduced to 0.7 mL / min, and the coating liquid is atomized and evenly sprayed on the surface of the core (22 g of core and about 120 mL of coating liquid). The reaction is carried out at 800 °C for 2 h to form a Na3V2(PO4)3 coating layer.

[0053] Example 6 The difference between this embodiment and Embodiment 1 lies in step three: the preparation of the elastic buffer layer (PVDF-HfO2): 1. Take 100 mL of NMP (N-methylpyrrolidone) and add 3 g of PVDF powder. Stir magnetically at 60 °C for 6 hours until a transparent and homogeneous gel is formed. Add 1 g of HfO2 nanoparticles and disperse using a high-speed disperser (6000 rpm) for 40 minutes to form a uniform buffer slurry. Then transfer the buffer slurry to a beaker and use a probe-type ultrasonic disperser, immersing the probe 1-2 cm below the liquid surface, in "intermittent ultrasonic" mode. Set "5 seconds on, 3 seconds off" for a total duration of 30 minutes. The viscosity of the buffer slurry is measured to be 700 mPa using a viscometer. s. 2. Buffer layer coating operation: The product coated in the second step is placed in a tube furnace. The temperature of the tube furnace is set to 100℃. The equipment is started, the atomizer frequency is adjusted to 9MHz, and the peristaltic pump flow rate is set to 0.7mL / min. The buffer layer slurry (19.0mL) is atomized and sprayed on its surface. It is kept at 80℃ for 2 hours. The product is taken out of the tube furnace and allowed to cool naturally to room temperature. Then it is placed in an 80℃ vacuum oven and dried for another 12 hours to prevent NMP residue. After that, it is gently ground with an agate mortar (to avoid damaging the buffer layer) and passed through a 200-mesh sieve to obtain the final positive electrode material with a porous core, conductive outer layer and elastic buffer layer.

[0054] Example 7 The difference between this embodiment and Embodiment 1 lies in step three: the preparation of the elastic buffer layer (PAA-TiO2): 1. Take 100 mL of deionized water and add 3 g of polyacrylic acid (PAA) powder. Stir magnetically at 50°C for 60 min until the PAA is completely dissolved, forming a transparent, high-viscosity solution. Add 1 g of TiO2 nanoparticles and disperse using a high-speed disperser (6000 rpm) for 40 min to form a uniform buffer layer slurry. The viscosity of the buffer layer slurry is measured to be 700 mPa using a viscometer. s.

[0055] 2. Buffer layer coating operation: Place the coated product from the second step into a tube furnace, set the temperature of the tube furnace to 100℃, start the equipment, adjust the atomizer frequency to 9MHz, set the peristaltic pump flow rate to 0.7mL / min, atomize the buffer layer slurry (19.0mL) and spray it on its surface, keep it at 100℃ for 2 hours, remove the product from the tube furnace, let it cool naturally to room temperature, then gently grind it with an agate mortar (to avoid damaging the buffer layer), and pass it through a 200-mesh sieve to obtain the final positive electrode material with a porous core, a conductive outer layer, and an elastic buffer layer.

[0056] Comparative Example 1 The difference between this embodiment and Embodiment 1 is that steps two and three are omitted, resulting in an uncoated composite material.

[0057] Comparative Example 2 The difference between this embodiment and Embodiment 1 is that ferric nitrate is not added, resulting in NASICON material with only binary doping.

[0058] Comparative Example 3 The difference between this embodiment and Embodiment 1 is that in step one, 24.4g of ferric nitrate, 9.3g of manganese nitrate, 8.7g of chromium nitrate and 11.2g of glucose are placed in 300 mL of deionized water and placed on a magnetic stirrer (speed 1000 rpm) and stirred at room temperature for 40 min until completely dissolved to form a mixed solution; and steps two and three are omitted to obtain the carbon-coated cathode material.

[0059] Comparative Example 4 The difference between this embodiment and Embodiment 1 is that step three is omitted, resulting in a composite material that is only coated with Na2Ti3O7.

[0060] Comparative Example 5 The difference between this embodiment and Embodiment 1 is that step two is omitted, and the 22g of porous core powder prepared in the first step is directly used to prepare the elastic buffer layer (PI-Al2O3) in the third step, thus obtaining a composite material coated only with PI-Al2O3.

[0061] Battery assembly testing The positive electrode materials prepared in Examples 1-7 and Comparative Examples 1-5, Super-P conductive carbon black, and PVDF binder were mixed in a mass ratio of 8:1:1 and placed on a magnetic stirrer for 24 hours to obtain an active material slurry. The slurry was then coated onto the surface of aluminum foil (coating amount of 10 mg / cm²). 2 The electrodes were then vacuum-dried at 70 °C for 24 h. Finally, the electrodes were cut into circular electrode sheets with a diameter of 10 mm and a thickness of 8-10 mm using a slicer. A sodium metal sheet was used as the counter electrode, glass fiber was used as the separator, and the electrolyte was 1 mol / L NaPF6 (EC:DEC = 1:1, volume ratio), with an electrolyte injection volume of 30 μL. The electrodes were then assembled into a battery.

[0062] Depend on Figure 1 It can be seen that, except for the positive electrode material prepared in Comparative Example 1 which is spherical, the others all exhibit a rod-like structure, indicating that the addition of the coating layer has a certain influence on the nucleation of the material. Furthermore, the positive electrode material prepared in Example 1 has a uniform particle distribution, regular morphology, and less agglomeration, and has more pores. The positive electrode materials prepared in Examples 2 and 3, on the other hand, exhibit more agglomeration and inconsistent particle size.

[0063] from Figure 2As can be seen, the cathode material prepared in Example 1 has the smallest radius of curvature in the high-frequency region and the largest linear slope in the low-frequency region. This indicates that the electrode material has the smallest charge transfer resistance and the lowest electrochemical and concentration polarization. This set of data directly verifies the rationality of the porous core + conductive layer + PI-Al2O3 elastic buffer layer design. Without affecting electron conduction, through interface optimization and structural support, the resistance to ion transport and charge transfer is significantly reduced, providing kinetic assurance for the high rate and cycle performance of the battery.

[0064] The batteries corresponding to Example 1 and Comparative Example 1 were cycled 200 times at a rate of 0.2C at room temperature. Figure 3 As shown, the positive electrode sheet prepared using the positive electrode material of Comparative Example 1 exhibits slight cracks on its surface, which has a certain impact on the entire conductive network. In contrast, the positive electrode sheet prepared using Example 1 shows no obvious cracks on its surface, indicating that the conductive outer layer and the elastic buffer layer form a dense coating, suppressing microcracks during cycling. Furthermore, the battery corresponding to Example 1 retains 97.45% of its capacity after 200 cycles, while the battery corresponding to Comparative Example 1 retains 95.22% of its capacity after 200 cycles; thus, the battery corresponding to Example 1 exhibits better cycle performance.

[0065] Referring to Table 1 below, the initial discharge capacity of Example 1 was 148 mAh at rates of 0.1, 1, and 5 C. g 1 118 mAh g 1 and 77 mAh g 1 This is significantly higher than the 120 mAh of Comparative Example 1. g 1 80 mAh g 1 and 42 mAh g 1 .

[0066] like Figure 5 The XRD patterns of the composite materials obtained after the conductive outer layer (Na2Ti3O7) coating process in Examples 1-3 are shown. The XRD peaks of the composite materials are basically consistent with the characteristic peaks of the Na2Ti3O7 standard card, and the peaks are sharp, indicating that the process completely generates the Na2Ti3O7 coating.

[0067] Table 1

[0068] Specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various changes or modifications within the scope of the claims, which do not affect the essence of the present invention. Unless otherwise specified, the embodiments and features described in this application can be arbitrarily combined with each other.

Claims

1. A positive electrode material, characterized in that, The positive electrode material has a three-layer structure from the inside out: a porous core, a conductive outer layer, and an elastic buffer layer; wherein... The porous core is a multi-metal element-doped NASICON porous material, wherein the metal doping elements are Fe, Mn and Cr, and the molar ratio between Fe, Mn and Cr is 5:2-3:2-3; or the metal doping elements are Fe, Mn and V, and the molar ratio between Fe, Mn and V is 5:2-3:2-3. The conductive outer layer covers the porous core, and the conductive outer layer is Na2Ti3O7 or Na2Ti6O. 13 Na4Ti5O 12 Or Na3V2(PO4)3; The elastic buffer layer is AM m O n A is PI, PVDF or PAA, M is selected from Al, Hf or Ti, and 1≤m≤2, 2≤n≤3.

2. The cathode material according to claim 1, characterized in that, The chemical formula of the NASICON porous material is Na. (3+y) Fe x Mn y Cr z (PO4)3, where x+y+z=2.

3. The cathode material according to claim 1, characterized in that, M in the elastic buffer layer m O n It can be Al2O3, HfO2, or TiO2.

4. A method for preparing a cathode material according to any one of claims 1-3, characterized in that, The method includes the following steps: S1. Preparation of porous cores: S1-1. Add sodium dihydrogen phosphate to a mixed metal salt solution containing multiple metal ions, stir, and adjust the pH to 2-3; add a pore-forming agent, heat and stir until a precursor solution is formed, and filter for later use; S1-2: After the filtered precursor solution is ultrasonically atomized, the droplets are dried and then calcined to obtain multi-metal element doped NASICON porous material. S2, Conductive outer coating: Sodium hydroxide was added to the titanium source solution and stirred to form a stable coating solution. The coating solution was ultrasonically atomized and sprayed onto the surface of the porous core prepared by S1. The reaction was carried out at 700-800℃ to form a conductive coating layer and obtain the coating product. Alternatively, sodium acetate is added to the vanadium source solution and stirred to form a stable coating solution; the coating solution is then ultrasonically atomized and sprayed onto the surface of the porous core prepared by S1, and reacted at 700-800℃ to form a conductive coating layer to obtain the coating product. S3. Preparation of the elastic buffer layer: Add M to a solution containing PI, PVDF, or PAA m O n The powder is dispersed to form a buffer layer slurry; the buffer layer slurry is ultrasonically atomized and sprayed onto the surface of the coating product obtained in step S2, and then cured to obtain the positive electrode material.

5. The method for preparing the cathode material according to claim 4, characterized in that, Step S1-1 includes at least one of the following technical features: A1. The mixed metal salt solution is a mixed aqueous solution of nitrates doped with metal elements; A2. The pore-forming agent is polyethylene glycol, and the mass ratio of polyethylene glycol to sodium dihydrogen phosphate is 1:5-8. And / or, steps S1-2 include at least one of the following technical features: B1. The ultrasonic atomization frequency is 12-18 MHz, and the peristaltic flow rate is 1-3 mL / min; B2. The drying temperature is 180-220 ℃, and the drying time is 4-6 hours; B3. The calcination temperature is 720-780 ℃, and the calcination time is 8-10 h; B4. The calcination is carried out in an inert atmosphere with a gas flow rate of 45-55 mL / min.

6. The method for preparing the cathode material according to claim 4, characterized in that, Step S2 includes at least one of the following technical features: C1. The preparation method of the titanium source solution is as follows: after adding tetrabutyl titanate to the solvent to dissolve it, the pH of the solution is adjusted to 1~2; Alternatively, the vanadium source solution can be prepared by adding ammonium metavanadate and ammonium dihydrogen phosphate to a solvent, stirring, then adding citric acid, and stirring until a clear solution is formed. C2. Before spraying the coating liquid onto the surface of the porous core prepared in S1 after ultrasonic atomization, the porous core prepared in S1 is kept at 250-350℃ for 30-40 min to remove surface adsorbed water. C3. The ultrasonic atomization frequency is 10-12MHz, and the peristaltic flow rate is 0.7-1mL / min.

7. The method for preparing the cathode material according to claim 4, characterized in that, Step S3 includes at least one of the following technical features: D1. The solution comprising PI, PVDF or PAA is prepared by adding PI, PVDF or PAA powder to a solvent, heating to 50-90°C, and stirring until PI, PVDF or PAA is at least partially dissolved to form a solution. D2, M m O n The mass ratio of PI, PVDF, or PAA is 1:2-4; D3. The dispersion speed is 5000-7000 rpm, and the dispersion time is 30-40 min; D4. The viscosity of the buffer layer slurry is 500~800 mPa•s; D6. The atomization frequency of ultrasonic atomization is 8-10 MHz, and the peristaltic flow rate is 0.6-0.8 mL / min; D7. After curing, the product is cooled to room temperature, ground, and sieved to obtain the positive electrode material.

8. A battery comprising the positive electrode material according to any one of claims 1-3, or comprising the positive electrode material prepared by the method according to any one of claims 4-7.

Citation Information

Patent Citations

  • Preparation method of three-dimensional porous vanadium phosphate sodium / carbon anode material

    CN105932277A

  • Positive electrode material, preparation method of positive electrode material, positive electrode and secondary battery

    CN116960288A

  • Core-shell structured positive electrode material and preparation method and application thereof

    CN118572049A